1997
DOI: 10.14430/arctic1105
|View full text |Cite
|
Sign up to set email alerts
|

Re-estimating the Size of the Polar Bear Population in Western Hudson Bay

Abstract: ABSTRACT. A mark-recapture study of polar bears (Ursus maritimus) ashore during the ice-free period of Hudson Bay was undertaken in 1994 and 1995 to re-estimate the size of the western Hudson Bay population. Previous estimates were based on animals caught between the Churchill and Nelson Rivers; consequently, bears in the southern part of the geographic range of this population were not sampled. We used Jolly-Seber models to re-estimate population size from two data sets: bears handled between the Churchill an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…The low densities at which polar bears occur and their relative invisibility against a background of white snow and ice have made capture-recapture the most common procedure used to estimate population size (Lunn et al, 1997;Stirling et al, 1999;Amstrup et al, 2001b;McDonald and Amstrup, 2001). Just as the Agreement was based upon the assumption that hunters share one population throughout the SBS, early population estimates were based upon the same assumption.…”
Section: Discussionmentioning
confidence: 99%
“…The low densities at which polar bears occur and their relative invisibility against a background of white snow and ice have made capture-recapture the most common procedure used to estimate population size (Lunn et al, 1997;Stirling et al, 1999;Amstrup et al, 2001b;McDonald and Amstrup, 2001). Just as the Agreement was based upon the assumption that hunters share one population throughout the SBS, early population estimates were based upon the same assumption.…”
Section: Discussionmentioning
confidence: 99%
“…This was an increase from 1997 scientific population estimates and from the previous target number of 1200 animals (Lunn et al, 1997). The population estimate was raised in the 2005 agreement because community consultations revealed that Inuit harvesters felt there were more bears than the surveys indicated, and they estimated nine more bears could be harvested per year.…”
Section: Introductionmentioning
confidence: 97%
“…During the summer and early autumn, our study area is frequented by a large proportion of the Western Hudson Bay population of polar bears which come ashore during the months when Hudson Bay is ice free (Stirling et al 1977;Derocher and Stirling 1990;Stirling et al 2004;Stapleton et al 2014a). Population dynamics and habitat use of this population has been extensively studied (e.g., Derocher and Stirling 1995;Lunn et al 1997;Regehr et al 2007;Cherry et al 2013), yet virtually nothing is known about polar bearhuman interactions outside communities in this region. In late summer and autumn, bears (primarily adult males) congregate at Cape Churchill in the north-eastern corner of the Park (Latour 1981).…”
Section: Study Sitementioning
confidence: 99%